(untitled) (Journal of Current and Advance Medical Research, 2020)
Background: The pattern of pulmonary venous flow due to left ventricular diastolic dysfunction is important among impaired glucose tolerance patients. Objectives: The purpose of the present study was to observe the pulmonary venous flow pattern due to left ventricular diastolic dysfunction among impaired glucose tolerance patients. Methodology: This cross sectional study was carried out in the Department of Cardiology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from July 2005 to June 2007. Impaired glucose tolerance (IGT) patients attending Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders, Dhaka, Bangladesh were included in this study as group A. The apparently healthy persons without cardiovascular disease were taken as group B. All the study subjects underwent 2D and M-mode echocardiography. Result: Doppler pulmonary inflow parameters of group A and group B showed no statistically’ significant difference in peak S-wave (46.42+10.06 vs 51.20±8.34 cm/s, P>0.05), peak D-wave (34.86±8.01 vs 40.48±5.77 cm/s, P>0.05) and S/D, ratio (1.35±0.21 vs 1.20±0.13, P>0.05). Doppler pulmonary inflow parameters were compared between left ventricular diastolic dysfunction present and absent in group A which showed no statistically significant differences in peak S-wave (p>0.01), peak D-wave (p>0.50), S/D ratio (p>0.05). Conclusion: In conclusion the pulmonary venous flow pattern is significantly difference due to left ventricular diastolic dysfunction among impaired glucose tolerance patients. Journal of Current and Advance Medical Research 2020;7(1): 3-6